Circular, Local, Open: A Recipe for Sustainable Building Construction - Asimina Kouvara; Christina Priavolou; Denise Ott; Philipp Scherer; Verena Helen van Zyl-Bulitta (Buildings, 2023)
In response to the construction sector’s contribution to the climate crisis and exacerbation of social inequalities, we explore sustainable alternatives in building construction, informed by the illustrative case study of the Polycare construction system. First, through a Life-Cycle Assessment (LCA) method, we show that the ecological footprint of circularity-oriented buildings based on polymer concrete is significantly lower than that of conventional cement concrete buildings. Despite the drawbacks of polymer concrete, its high-performance properties and the possibility to integrate secondary materials in its recipe can result in a reduced carbon footprint. When coupled with design-embedded modularity that facilitates circular processes (e.g., the disassembly and reuse of building components), buildings similar to those in the case study demonstrate potential for transitioning towards comprehensive sustainable building practices. Further, we discuss how this sustainability potential could be enhanced, drawing from interviews with Polycare’s stakeholders and key literature findings. In this direction, we provide a set of proposals anchored in the argument that threefold “circularity, localisation, and openness” is vital for sustainable and affordable alternatives, with openness being a crucial element for fostering innovation, adaptability, and scalability in building processes.